All-Optical NRZ-to-PRZ Format Conversion Limitations Using Notch Filters - Ozolins, Oskars; Trifonovs, Ilja; Parts, Rolands; Bobrovs, Vjaceslavs (Elektronika ir Elektrotechnika, 2015)
In this paper all-optical non-return to zero to pseudo-return to zero format conversion limitations, using optical notch filters, are evaluated numerically. Open source simulation toolbox Optilux was used for simulations. Gauss and short term integrator notch filter performance and full width half maximum bandwidth impact on format conversion at transmission speed up to 40 Gbit/s was compared. Then format conversion performance was evaluated in a cascade of single ring microring resonators. Results show that large depth of an optical notch filter can cause two pulses generation at the edges of input pulses and lead to clock signal degradation. DOI: http://dx.doi.org/10.5755/j01.eee.21.1.9807